2017
DOI: 10.5994/jei.14.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Toksisitas beberapa jenis fungisida komersial pada serangga penyerbuk, Trigona (Tetragonula) laeviceps Smith

Abstract: ABSTRAKSalah satu pestisida yang umum digunakan pada sistem perkebunan adalah fungisida. Walaupun spesifik didesain untuk mengatasi serangan cendawan, beberapa penelitian menunjukkan bahwa fungisida memiliki efek neurotoksik terhadap hewan uji. Hal ini memberikan potensi merugikan bagi hewan-hewan non target yang menguntungkan pada sistem pertanian, seperti serangga penyerbuk. Penelitian ini dilakukan untuk menentukan toksisitas dari fungisida yang beredar di pasaran pada salah satu agen penyerbuk Trigona (Tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Mineral oil may have augmented the effect of difenoconazole, since this adjuvant acts in the contact action mode (MAPA, 2018), while difenoconazole is a systemic action compound with high residual effect (Andrade Junior & Galbieri, 2014;Balardin, 2015). On the other hand, difenoconazole was classified as little toxic for Trigona (Tetragonula) laeviceps Smith by topical route (Kinasih et al, 2017), suggesting that this fungicide used without addition of adjuvants is considered nontoxic for bee survival. Nevertheless, the authors reported that this fungicide could cause secondary effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral oil may have augmented the effect of difenoconazole, since this adjuvant acts in the contact action mode (MAPA, 2018), while difenoconazole is a systemic action compound with high residual effect (Andrade Junior & Galbieri, 2014;Balardin, 2015). On the other hand, difenoconazole was classified as little toxic for Trigona (Tetragonula) laeviceps Smith by topical route (Kinasih et al, 2017), suggesting that this fungicide used without addition of adjuvants is considered nontoxic for bee survival. Nevertheless, the authors reported that this fungicide could cause secondary effects.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the use of pesticides affects pests and bee species (Della Lucia et al, 2014; Rondeau et al, 2014). RESEARCh ARTICLE -BEES Studies on acaricide fenpyroximate (Dahlgren et al, 2012;Li-Byarlay et al, 2014) have reported its toxicity on Apis mellifera L. Syromyatnikov et al (2017) and Kinasih et al (2017) also described the effects of the fungicide difenoconazole on Bombus terrestris L. and Trigona (Tetragonula) laeviceps Smith.…”
Section: Introductionmentioning
confidence: 99%
“…The test consisted of 3 treatments 1) insecticide A 100 ppm, 2) insecticide B 60 ppm, and 3) control (aquades only). To drip the liquid easier, the bees were anesthetized by placing them in the fridge (-10 o C) for 2 minutes [27]. Then, 1 µl of the solution was dripped on the thorax of the bee.…”
Section: Contact Toxicity Assay Of T Laevicepsmentioning
confidence: 99%
“…Fungisida kimiawi dengan bahan aktif tersebut mampu menekan pertumbuhan Cercospora capsici hingga 87,98% secara in vitro (Thejakumar dan Devappa, 2016). Namun, penggunaan fungisida kimiawi secara terus menerus dapat menyebabkan terjadinya resistensi pada jamur serta pencemaran (Sumardiyono, 2008), membunuh organisme nontarget dan mengganggu ekosistem (Kinasih et al, 2017).…”
Section: Pendahuluanunclassified